THE DEVELOPMENT GUDELINE FOR DESIRED CHARACTERISTICS OF STUDENT AT AMNUAYWIT NAKHON PATHOM SCHOOL - Surasakhon, Wirot; Pengnoo, Thidaporn; Napatthirachanchai, Chayanun; Dejbamrung, SomchaiI (Journal of MCU Nakhondhat, 2023)
The objectives of this research article were to: 1) the desired characteristics of students in Amnuaywit Nakhon Pathom School, and 2) the development guidelines for desired characteristics of students in Amnuaywit Nakhon Pathom School. This research is a mixed method research. The quantitative research, the population used in this study were 314 parents of elementary students in Amnuaywit Nakhon Pathom School. The sample size Determination Using Krejcie and Morgan Table. the sample group was 173 parents of elementary students in Amnuaywit Nakhon Pathom School. Research instruments employed were a questionnaire focusing on desired characteristics. Data analysis was conducted using frequency, percentage, arithmetic mean and standard deviation. The qualitative research, the key informants comprised 25 teachers in Amnuaywit Nakhon Pathom School and 12 parents of students in Amnuaywit Nakhon Pathom School. Research instruments employed were Semi-structured Interview and focus group discussions to address development guidelines for the desired characteristics of students in Amnuaywit Nakhon Pathom School. Data analysis was conducted using content analysis. The research findings were as follows: The desired characteristics of students in Amnuaywit Nakhon Pathom School were generally at a high level. Upon examining each aspect, six aspects were identified as being at a high level, while two aspects were at an average level. Ordered from highest to lowest mean, these aspects were: patriotism religion and monarchy, moral integrity, public-mindedness, active learning, appreciation of Thai culture, and disciplined behavior. The two average aspects included: commitment to work and sufficiency. 2)The development guidelines for desired characteristics of students in Amnuaywit Nakhon Pathom School suggested that schools should organize projects and activities aimed at instilling and reinforcing the eight desirable characteristics among learners. Furthermore, it was recommended that content and stories related to these eight desirable characteristics be integrated into the learning management of all subjects.